Romeo and Juliet [videorecording] - Luhrmann, Baz; Martinelli, Gabriella (Bookmark Production, 1996)
Baz Luhrmann's adaptation of William Shakespeare's classic love story. A retelling of the world's most tragic love affair. But the setting has been moved from its Elizabethan origin to the futuristic urban backdrop of Verona Beach.